Two Approaches in Computer Simulation of the MFM-images - E.A. Mozharova; K.V. Nefedev (Журнал нано- та електронної фізики)
Two approaches to the interpretation of the data of magnetic force microscopy are considered. The first approach involves the reconstruction of the magnetization distribution in the researched samples on the base of an assumption about the magnetic state and the subsequent numerical magnetic force microscopy experiment. The second is related to an experimental data processing.